Revitalizing Cooperative Human Resources: An Education and Perspective Analysis, Study at Medan Municipal City; Indonesia - Nainggolan, Karlonta; Parulian, Tohap (International Journal of Scientific Research and Management (IJSRM), 2018)
Main conclusion of our first year research in Medan Municipal city is, Revitalizing Cooperatives, has to be start by revitalizing cooperatives’ human resources. In second year of our   research, we did experimental study by grouping sample in to treatment and no treatment cooperatives, then implementing the revitalization model that we had developed in first year. The aims of this research are:1) to measure the achievement level between cooperative treatment versus no treatment, in building Motivation, Commitment, and Integrity (MCI) after education/ training program, and 2.a) to measure the perspective differences among cooperatives treatment, in how important it is to develop and to apply Cooperative Principle and Values (CPV), from the MCI perspective,  2.b) Do perspective differences also reflect the achievement level in building MCI, to develop and to apply variables dimension (CPV).   It is found, achievement level of treatment cooperative in building MCI, is significantly different from no treatment. It is also found, there is a perspective differences among cooperative treatment in how important it is to develop and to apply CPV.  But, although mean-differences is indifferent, it is not always mean they have an indifferent level of achievement in building MCI, to develop and to apply CPV; and vice versa different perspective is not necessary mean, they have different level of achievement, in terms of “good” with   = > 0.375 or “bad” with  = < 0.375.  This study also reveals that: 1) character issues and organizational conflict have a very prominent effect in developing MCI, 2) continuing education is important in the process of revitalizing cooperatives human resources. These findings, support our conclusion in first year research